2020
DOI: 10.1002/joc.6639
|View full text |Cite
|
Sign up to set email alerts
|

New hourly extreme precipitation regions and regional annual probability estimates for the UK

Abstract: Recent flooding related to extreme precipitation in the UK has highlighted the importance of better understanding these events. Many studies have quantified annual exceedance probabilities (or return periods) for UK extreme daily precipitation using fixed regions (e.g., HadUKP) and region of interest (ROI) (e.g., Flood Estimation Handbook) approaches, although fewer have evaluated short-duration events, which are important for flash flooding. Existing UK extreme precipitation regions are based on daily dataset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 82 publications
0
24
0
Order By: Relevance
“…Similar work over the Netherlands has shown that most hourly precipitation extremes are part of large-scale circulation systems [29]. Large-scale drivers of hourly precipitation extremes have been explored further, by linking these to atmospheric circulation patterns over Europe [30,31], the US [32], Australia [33] and globally [34]. Analysis of CPMs has established the large-scale precursors of small-scale storms over the UK [35].…”
Section: Introductionmentioning
confidence: 99%
“…Similar work over the Netherlands has shown that most hourly precipitation extremes are part of large-scale circulation systems [29]. Large-scale drivers of hourly precipitation extremes have been explored further, by linking these to atmospheric circulation patterns over Europe [30,31], the US [32], Australia [33] and globally [34]. Analysis of CPMs has established the large-scale precursors of small-scale storms over the UK [35].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, efforts to adjust this guidance to account for climate change vary greatly from country to country. Many jurisdictions do not provide any flood guidance related to climate change [2,10], while others have mature guidance that is continually being updated as new evidence becomes available [4,59]. Here, we provide a practical and pragmatic review of flood estimation methods in the face of climate change and provide recommendations for future research directions and flood guidance, with a focus on flood estimation practice.…”
Section: Introductionmentioning
confidence: 99%
“…Work across the Netherlands has also shown that most hourly precipitation extremes are part of large-scale circulation systems, with considerable forcing from larger scales [ 6 ]. These large-scale drivers of hourly precipitation were linked to atmospheric circulation patterns over Europe [ 7 , 8 ], the USA [ 9 ], Australia [ 10 ] and globally [ 11 ], with convection-permitting models (CPMs) over the UK showing that large-scale stability is skilful in predicting the occurrence of subdaily rainfall extremes [ 12 ].…”
mentioning
confidence: 99%